2022
DOI: 10.3390/jcdd9040119
|View full text |Cite
|
Sign up to set email alerts
|

Lipopolysaccharide Modifies Sodium Current Kinetics through ROS and PKC Signalling in Induced Pluripotent Stem-Derived Cardiomyocytes from Brugada Syndrome Patient

Abstract: Studies have suggested a connection between inflammation and arrhythmogenesis of Brugada syndrome (BrS). However, experimental studies regarding the roles of inflammation in the arrhythmogenesis of BrS and its underlying mechanism are still lacking. This study aimed to investigate the influence of inflammation on BrS-phenotype features using human-induced stem cell-derived cardiomyocytes (hiPSC-CMs) from a BrS-patient carrying an SCN10A variant (c.3749G > A). After LPS treatment, the peak sodium current dec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 54 publications
0
3
0
Order By: Relevance
“…Detrimental effects of endotoxemia on cardiac contractility are largely due to mitochondrial dysfunction that leads to abnormal calcium handling, disruption of ATP synthesis, endothelium reticulum stress, and autophagy. Furthermore, LPS leads to electrophysiological dysfunctions through a both a direct and cytokine-mediated effect on sodium current kinetics and non-selective cation channel transient receptor potential vanilloid 1 (TRPV1) [ 34 , 35 , 36 , 37 ]. Furthermore, LPS and its downstream mediator TNF-α, IL-1β, IL-6, and C5a and ROS [ 38 , 39 ] critically alter calcium (Ca ++ ) homeostasis by blunting the amplitude of intracellular currents and concentrations.…”
Section: Pathophysiology Of Septic Cardiomyopathymentioning
confidence: 99%
“…Detrimental effects of endotoxemia on cardiac contractility are largely due to mitochondrial dysfunction that leads to abnormal calcium handling, disruption of ATP synthesis, endothelium reticulum stress, and autophagy. Furthermore, LPS leads to electrophysiological dysfunctions through a both a direct and cytokine-mediated effect on sodium current kinetics and non-selective cation channel transient receptor potential vanilloid 1 (TRPV1) [ 34 , 35 , 36 , 37 ]. Furthermore, LPS and its downstream mediator TNF-α, IL-1β, IL-6, and C5a and ROS [ 38 , 39 ] critically alter calcium (Ca ++ ) homeostasis by blunting the amplitude of intracellular currents and concentrations.…”
Section: Pathophysiology Of Septic Cardiomyopathymentioning
confidence: 99%
“…These include long-term culture, culture on a rigid substrate [ 65 , 66 ], electrical and mechanical stimulation [ 67 , 68 ], and the use of biochemical cues such as the growth hormone Tri-iodo-L-thyronine [ 69 ]. These advancements refined the iPS-CM technique and have allowed the production and characterisation of iPSCs leading to a deeper understanding of different ion channels involved in BrS, including L-type Ca 2+ channels [ 70 , 71 ], the tetrodotoxin (TTX)-resistant Na + voltage-gated channel alpha subunit 10 ( SCN10A ) [ 72 , 73 ], and K + channels including the K + voltage-gated channel subfamily Q member 1 ( KCNQ1 ) and the K + voltage-gated channel subfamily H member 2 ( KCNH2 ) [ 3 , 74 ].…”
Section: Brugada Syndrome Experimental Modelsmentioning
confidence: 99%
“…The data showed that after 48 h of incubation, the patient-derived cells displayed a decrease in the already impaired Na + peak current density and small but significant changes in channel kinetics compared to control cells derived from three healthy donors. Additionally, the effect was prevented by the protein kinase C (PKC) inhibitor chelerythrine, indicating that inflammation may worsen LoF Na + variants in BrS patients through enhanced reactive oxygen species (ROS)-PKC signalling [ 73 ]. In a separate study, Belbachir and colleagues identified a variant in the Ras associated with diabetes (RAD) guanosine triphosphatases (GTPase) gene ( RRAD ) in a BrS patient, derived iPSC-CMs and found a reduction in the velocity of the AP upstroke, prolonged AP duration, and increased probability of early afterdepolarisations (EADs), as well as a reduction in Na + and Ca 2+ peak current densities and increased late I Na .…”
Section: Brugada Syndrome Experimental Modelsmentioning
confidence: 99%